COLLABORATIVE GOVERNANCE IN WASTE MANAGEMENT AT THE SIDENRENG RAPPANG REGENCY ENVIRONMENTAL AGENCY - Akmes, Riska; Yamin, Muh Nur; Nur, Andi Cudai (Universitas Negeri Makassar, 2025)
This study aims to find out the process of Collaborative Governance in Waste Management at the Environment Agency of Sidenreng Rappang Regency. This research includes descriptive qualitative research with data collection techniques through observation, interviews, literature studies and documentation. Data analysis techniques consist of data reduction, data presentation and conclusion drawn.The results of this study show that the Collaborative Governance process in Waste Management at the Sidenreng Rappang Regency Environment Agency focuses on the initial conditions, the collaborative process so that it produces outcomes (results) from the collaboration process that has been implemented and running, but it is still not optimal. The initial condition for the formation of collaboration is the high generation of waste compared to waste management which is relatively low in Sidenreng Rappang Regency. There are 5 (five) indicators of the collaborative process that are considered in looking at the collaboration process, namely face-to-face dialogue, building trust, commitment in the process, mutual understanding and intermediate (middle) results. Of the five indicators, the obstacles are the indicators of mutual understanding and intermediate (middle) results because there are still components of society that do not dispose of waste in their place, this reflects not carrying out their responsibilities according to the direction and agreement on the division of tasks. So that the results obtained are the implementation of the collaboration process, but it still needs to be optimized for mutual understanding and intermediate results in active participation and contribution to the common interest to realize that waste management in Sidenreng Rappang Regency is running well.